Effects of a topical treatment with spleen tyrosine kinase inhibitor in healthy subjects and patients with cold urticaria or chronic spontaneous urticaria: Results of a phase 1a/b randomised double‐blind placebo‐controlled study. Issue 12 (18th June 2021) - Dickson, Marion C.; Walker, Alexandra; Grattan, Clive; Perry, Hayley; Williams, Nicola; Ratia, Nirav; Dewit, Odile; Gisbert, Sophie; Metz, Martin; Maurer, Marcus
Abstract : Aims: To explore the safety, tolerability, pharmacokinetics and pharmacodynamics (PD) of GSK2646264 using skin challenge models. Methods: Healthy volunteers (HV) with a positive allergen skin prick test received GSK2646264 (0.5% or 1% ww) and placebo creams on up to 10% body surface area (BSA). Cold (ColdU) or chronic spontaneous (CSU) urticaria patients received 1% GSK2646264 or placebo on up to 10% BSA. PD assessments included weal characteristics after skin allergen challenge, critical temperature threshold (CTT) in ColdU patients and defined area urticaria activity score in CSU patients. Results: Thirty‐four patients were randomised (17 HV, 12 ColdU, 5 CSU). Topical application of GSK2646264 and placebo was well tolerated. Systemic pharmacokinetics (AUC [0–24] h*ng/mL) was similar between HVs (Geomean 97.9 [%CV 37]) and ColdU patients (Geomean 68.2 [%CV 14; 3.5% BSA] or 167 [%CV 120; 10% BSA]). Whilst in HVs a similar reduction in skin allergen challenge weal area was observed following 3 applications of GSK2646264 and placebo, a trend towards a greater reduction was seen in ColdU with GSK2646264 compared to placebo. A clinically meaningful reduction in CTT, in ColdU patients treated with GSK2646264, was observed in 4 of 9 patients, who demonstrated either a complete inhibition of ColdU to ≤4°C ( n =  2) or partial response (reduction by >4°C, n =  2). Due to the small number of CSU patients recruited, no meaningful conclusions could be drawn from the defined area urticaria activity score PD endpoint. Conclusion: This Phase 1/1b study confirms that GSK2646264 cream applied topically penetrates the skin and some reduction in CTT was observed. (NCT02424799)